2022
DOI: 10.3390/biomedicines10051160
|View full text |Cite
|
Sign up to set email alerts
|

Altered Ocular Surface Health Status and Tear Film Immune Profile Due to Prolonged Daily Mask Wear in Health Care Workers

Abstract: Prolonged daily face mask wearing over several months might affect health of the ocular surface and is reported to be associated with complaints of discomfort and dry-eye-like symptoms. We studied the ocular surface clinical parameters, tear soluble factors and immune cell proportions in ophthalmologists practicing within similar environmental conditions (n = 17) at two time points: pre-face-mask period (Pre-FM; end of 2019) and post-face-mask-wearing period (Post-FM; during 2020 COVID-19 pandemic), with conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Hypercapnia also is known to induce inflammation, although the effects on the ocular surface have not been thoroughly investigated [ 17 ]. Nevertheless, D'Souza et al hypothesized that the increased carbon dioxide in the exhaled air flowing over the ocular surface may induce hypercapnia-related changes and alter the molecular profile [ 18 ]. The exhaled air is usually warmer than the environment and these changes in temperature might also promote tear evaporation [ 19 ].…”
Section: Possible Underlying Pathophysiological Mechanismsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hypercapnia also is known to induce inflammation, although the effects on the ocular surface have not been thoroughly investigated [ 17 ]. Nevertheless, D'Souza et al hypothesized that the increased carbon dioxide in the exhaled air flowing over the ocular surface may induce hypercapnia-related changes and alter the molecular profile [ 18 ]. The exhaled air is usually warmer than the environment and these changes in temperature might also promote tear evaporation [ 19 ].…”
Section: Possible Underlying Pathophysiological Mechanismsmentioning
confidence: 99%
“…Large surveys have used non-standardized questionnaires, although other authors have observed an increase in Ocular Surface Disease Index (OSDI) scores with the use of face masks [ 18 , [43] , [44] , [45] , [46] , [47] ]. This increase was mainly due to an increase in the discomfort and the vision scales [ 18 ].…”
Section: Effects Of Face Mask Use On the Ocular Surface Of Healthy In...mentioning
confidence: 99%
See 3 more Smart Citations